2013
DOI: 10.1007/s10554-013-0323-6
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative left atrial strain predicts post-operative atrial fibrillation in patients undergoing aortic valve replacement for aortic stenosis

Abstract: Post-operative atrial fibrillation (AF) is a common and serious complication in patients undergoing aortic valve replacement (AVR). Speckle tracking echocardiography (STE) has recently enabled the quantification of longitudinal myocardial left atrial (LA) deformation dynamics. Our aim was to investigate LA preoperative mechanical function in patients undergoing AVR for aortic stenosis using STE and determine predictors of post-operative AF. 76 patients with aortic stenosis in sinus rhythm, undergoing AVR, were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(67 citation statements)
references
References 30 publications
0
67
0
Order By: Relevance
“…18 Cameli et al reported that in patients undergoing AVR for AS, LAVI and the peak LA longitudinal strain measured by STE were predictors of POAF in their univariate analysis. 19 Furthermore, in their multivariate regression analysis, age and peak LA longitudinal strain (but not LAVI) were independent predictors of POAF. Moreover, ROC curve analysis showed that the AUC of peak LA longitudinal strain (0.89) showed higher diagnostic accuracy than the AUC of LAVI (0.78).…”
Section: Study Limitationsmentioning
confidence: 94%
“…18 Cameli et al reported that in patients undergoing AVR for AS, LAVI and the peak LA longitudinal strain measured by STE were predictors of POAF in their univariate analysis. 19 Furthermore, in their multivariate regression analysis, age and peak LA longitudinal strain (but not LAVI) were independent predictors of POAF. Moreover, ROC curve analysis showed that the AUC of peak LA longitudinal strain (0.89) showed higher diagnostic accuracy than the AUC of LAVI (0.78).…”
Section: Study Limitationsmentioning
confidence: 94%
“…(12) Area-length method and biplane method of discs (modified Simpson's rule) were recommended recently as well as a 3D data set. (10) With the development of echocardiographic speckle tracking imaging, (18) left atrial function assessment became possible (19) with calculation of segmental and average peak left atrial strain, (20,21) but this is time consuming and needs off-line analysis. Echocardiographic 3D data sets are usually obtained from the apical approach using a multi-beat full volume acquisition.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with severe aortic stenosis (AS), left atrial (LA) enlargement and dysfunction are associated with the evolution of symptoms, the recurrence of heart failure after aortic valve replacement,(1) the development of early postoperative atrial fibrillation (AF) (2), and mortality. (3) Transcatheter aortic valve implantation (TAVI) is now considered the treatment of choice for patients with severe AS at high risk for open-heart surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Patients were included if transthoracic echocardiograms obtained before and at medium-term follow-up (between 2 to 12 months) were available for review. Exclusion criteria were: (1) the presence of AF during the echo study (since atrial mechanics cannot be adequately assessed) or (2) inadequate endocardial definition of the LA walls, resulting in poor speckle-tracking. The control group consisted of 20 patients ≥ 75 years with no significant underlying heart disease (based on clinical and echo assessments).…”
Section: Introductionmentioning
confidence: 99%